The Meaning of Theodor Storm's Poem Die Stadt: A Riffaterrean Semiotic Analysis - Salva Zulfa Khalisa; Uryadi Rohimin; Azizah Hanoum Siregar (Universitas Negeri Malang, 2026)
Understanding literary meaning is a key competency for German literature students, especially in poetry analysis. One of the challenges that often arises is the difficulty in interpreting symbolic meanings and indirect expressions in poetic texts. As a solution to this problem, this study analyzes Theodor Woldsen Storm's poem Die Stadt using Riffaterre's semiotic approach to reveal deeper meanings. A heuristic reading reveals a small town by the sea that was the backdrop of Storm's youth. A hermeneutic reading shows that the town symbolizes Storm's longing for Husum. Indirect expressions in this poem include metaphors, personification, synecdoche, ambiguity, contradictions, mixed rhyme patterns, and enjambment. The matrix of this poem is Heimatsehnsucht, with the model “Doch hängt mein ganzes Herz an dir”, while its potential hypogram is Heimatsehnsucht and its actual hypogram is Oktoberlied.